2004
DOI: 10.1016/j.jtcvs.2003.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Thromboembolic events after aortic valve replacement in elderly patients with a Carpentier-Edwards Perimount pericardial bioprosthesis

Abstract: Some emboli seemed triggered by the valve prosthesis. A proper anticoagulant protocol but also a treatment of hypertension is important in the prevention of thromboembolism after aortic valve replacement with a bioprosthesis. We did not find a significant role of atrial fibrillation and carotid artery disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
2

Year Published

2005
2005
2012
2012

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 20 publications
1
20
0
2
Order By: Relevance
“…Some studies reported on the predictors for thromboembolism after AVR on long-term and n o n e r e p o r t e d o n s u c h e v e n t s o n s h o r t -t e rm. The short-term thromboembolic events, however, have their importance since these are a predictor for future events (21). A preoperative CVA seemed to have a comparable significance (21-24) for long-term events.…”
Section: Thromboembolic Eventsmentioning
confidence: 95%
See 3 more Smart Citations
“…Some studies reported on the predictors for thromboembolism after AVR on long-term and n o n e r e p o r t e d o n s u c h e v e n t s o n s h o r t -t e rm. The short-term thromboembolic events, however, have their importance since these are a predictor for future events (21). A preoperative CVA seemed to have a comparable significance (21-24) for long-term events.…”
Section: Thromboembolic Eventsmentioning
confidence: 95%
“…Carotid artery disease could be a matter for debate. In some series (23,24), it was identified as a predictor for thromboembolism, in other series, this was not (21). A Doppler-duplex investigation is a reliable tool for the detection of lesions and is routinely performed in some institutions.…”
Section: Thromboembolic Eventsmentioning
confidence: 99%
See 2 more Smart Citations
“…A few retrospective studies and two randomized trials have examined the effects of various regimens on the incidence of postoperative thromboembolisms and hemorrhages after AVR with bioprostheses [22,[35][36][37][38][39][40][41][42][43][44][45][46]. Heras et al observed an inordinately high rate of early thromboembolic events in patients who were not anticoagulated, particularly after MVR in the first 10 days postoperatively [22].…”
Section: Literature Reviewmentioning
confidence: 99%